The role of the obesity in the primary hypertension course among men and women - Nadashkevych, O. N.; Kit, Z. M.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Nadashkevych O. N., Kit Z. M., Zukow W. The role of the obesity in the primary hypertension course among men and women. Journal of Education, Health and Sport. 2015;5(2):218-224. ISSN 2391-8306. DOI: 10.5281/zenodo.16094 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A218-224 https://pbn.nauka.gov.pl/works/546171 http://dx.doi.org/10.5281/zenodo.16094 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. UDC:616.12-008.331.1-056.52-036-055.1/.2 The role of the obesity in the primary hypertension course among men and women Nadashkevych O. N.1, Kit Z. M.1, Zukow W.2 1Danylo Halytsky Lviv National Medical University, Lviv, Ukraine 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland Abstract. With the objective to study peculiarities of AH with obesity into the research included 60 patients, among them 45 women and 15 men, among all of them examined features of vasodilatation group, measured leptin and endothelin-1(ЕТh-1) levels. Detected AH accompanied by obesity peculiarities of course of in dependence from the gender. Among men leptin and ЕТh-1 levels were more favorable for blood pressure correction. Among women increasing leptin and ЕТh-1 levels accompanied by decreasing of nitric oxide levels is a negative process, what is necessary to take into consideration when prescribing antihypertensive therapy what needs additional new drugs for correction of endothelial dysfunction. Key words: arterial hypertension, obesity, leptin.